Patient Satisfaction with Primary Health Care Services in Riyadh, Saudi Arabia - Albaqami NM; Alshagrawi S (International Journal of General Medicine)
Naif Mohammed Albaqami,1 Salah Alshagrawi2 1Family Medicine Department, Security Forces Hospital Program, Riyadh, Saudi Arabia; 2Department of Public Health, College of Health Sciences, Saudi Electronic University, Riyadh, Saudi ArabiaCorrespondence: Salah Alshagrawi, Email sshagrawi@gmail.comBackground: Patient satisfaction emerges as an indicator for enhancing the quality of health organizations, facilitating the evaluation and identification of the most significant characteristics of patient experience and their corresponding satisfaction levels. This can guide decisions to improve healthcare services and develop policies for better care. This study seeks to assess the level of patient satisfaction with primary healthcare (PHC) services in a large military hospital in Riyadh, Saudi Arabia, and to determine the extent of association between the level of satisfaction and patients’ social and demographic factors.Methods: A cross-sectional study was carried out on a convenient sample who received primary health care at the Security Forces Hospital in Riyadh, Saudi Arabia, between January and June 2023. Comparisons between qualitative variables were made using the chi-square to test significance and the One-Way ANOVA test was used to compare the means of total patient satisfaction scores, p < 0.05 was considered significant.Results: Among the 379 participants, 268 (70.7%) were males, 271 (71.2%) were married, 222 (58.6%) were military personnel, and 207 (54.6%) were between the ages of 31 and 49. The average satisfaction with PHC clinics was 52.1 (SD=4.9, highest score=60) while the average satisfaction with general evaluation was 27.6 (SD=3.4, highest score=35). Male participants exhibited greater satisfaction levels (M= 117.8, SD=12.8) than their female counterparts (M= 115.7, SD=15.3, p-value = 0.01). Patients aged 18– 30 had greater satisfaction levels (M= 117.5, SD=16.8, p-value = 0.02). Individuals who were single reported higher levels of satisfaction (M= 118.3, SD=16.2, p-value = 0.001). Participants with lower earnings (less than 5000 SR) had greater satisfaction levels compared to individuals having a greater income (p-value = 0.002).Conclusion: Patients attending a PHC center in a large military hospital in Riyadh generally reported high levels of satisfaction, particularly among male, single, younger, and low-income individuals. Despite these favorable results, several aspects of healthcare need enhancement to fulfill patient expectations and guarantee optimal healthcare provision. Therefore, healthcare practitioners must persist in determining and addressing these areas to guarantee that patients obtain optimal care and experience in primary healthcare clinics.Keywords: patient satisfaction, health services, quality management, primary health care, healthcare quality